Bypassing primary antiretroviral therapy centres in Sub-Saharan Africa: An integrative review of the theoretical and empirical literature - Maximillian Kolbe Domapielle; Sadat Zakari Abugbila; Marshall Kala (Journal of Virus Eradication)
The uptake of antiretroviral therapy (ART) is critical to meeting the global HIV treatment goal of 95-95-95 by 2025. Although a few Sub-Saharan African countries have already achieved this target, the prevalence of bypassing primary ART centres in many countries in the subregion has negative implications for ART uptake and use. This study used the access to health services framework to analyse the evidence and factors contributing to bypassing primary ART centres by individuals in the sub-region seeking HIV care and support. We found compelling evidence of the prevalence of ART clients bypassing their primary ART centres in search of specialised care in higher-tiered health facilities. Others use bypassing to conceal their HIV-positive status to avoid social stigma. We argue that introducing specialised and differentiated ART at the primary level of care can address this phenomenon. While we anticipate that this measure will satisfy clients' desire for specialised care, we recommend enhancing public awareness about the effectiveness of ART to reduce stigma towards ART clients. Legislation and strict enforcement of anti-HIV stigma laws, which outlaw and criminalise stigmatising people living with HIV (PLHIV), could potentially be an effective stigma-deterring measure. To complement this effort, PLHIV should be empowered to understand legislative instruments and steps to take when confidentiality and discriminatory issues arise. We recommend further research in Sub-Saharan Africa to investigate the relationship between bypassing primary ART centres and client adherence. The findings will help design appropriate strategies to increase ART uptake at primary ART centres.